Fault Detection in Sugarcane Crop Lines Using Hough Transform - Carneiro, Alexsandro M.; Higa, Gabriel T. H.; Rodrigues, Alexandre G. de O.; M. Junior, José; Pistori, Hemerson (Anais do Workshop de Visão Computacional (WVC), 2023)
In this work, we present an algorithm for detecting faults in sugarcane planting rows using the Hough transform, supported by image pre-processing techniques, such as binarization, morphological operators, filters, and skeletonization. Seven preprocessing calibration parameters are investigated. For the calibration and testing of the proposed method, a set of images with 589 samples, captured by UAV in an area located in Nova Andradina, MS, is presented.